Evaluating the Links between Relationship Marketing and Customer Loyalty in the Malaysian Retailing Industry - Phua, Tin Chew (2012)
In today market, organizations from retail industry are fighting for survival in today’s intense market place. Such dynamic challenges placed loyalty customer as an important asset to maintain the retail store’s success. Thus, the strategies that retailers using to build and to maintain the relationship with customers are extremely important. Therefore, this research is conducted to evaluate the link between Relationship Marketing and Customer Loyalty in the Malaysian retailing industry. Based on a detailed literature review, research constructs and a proposed model is developed. A quota sampling methodology, questionnaire survey is conducted to target 400 respondents from Petaling Jaya, Subang Jaya and Klang. The SPSS 17.0 is employed to test the hypotheses in accordance with the research objective. Results reveals that “Trust”, “Commitment”, “Relationship Strength” and “Service Quality” has significant positive relationship with customer loyalty. Recommendations to retailers and suggestions for future study are provided at the end of this paper.